Shared personal reflections on the need to broaden the scope of conservation social science. Issue 4 (7th August 2019) - Moon, Katie; Adams, Vanessa M.; Cooke, Benjamin
Abstract: Social science has a more diverse and meaningful role to play in conservation science and ecology than is currently being published within this field. We reflect on our personal research experiences to demonstrate how our in‐field learning has provided us with shared understandings of the importance of a broader engagement with social science methods, methodologies and philosophy. We focus on the value that comes from understanding that social science is not just answers, but stories ; not just data, but meaning ; and that place is a critical part of understanding socio‐ecological phenomena and processes. We engage in a shared process of reflexivity of our doctoral research experiences to show the potential of social science beyond its predominant positivist applications in the conservation science and ecology literature. We each discuss our experiences of our social science research endeavours in the context of private land conservation. We then distil our experiences into three themes that aim to advance social science engagement for conservation scientists: the partiality of knowledge, situating research within socio‐ecological context and researcher positionality. We conclude by acknowledging that as researchers we are not the exclusive authority on knowledge; that a deep understanding of conservation and ecology challenges might not provide simple or reducible answers that can be abstracted and applied universally; and that we must reflect on the possibilities for a more plural and diverse research practice for conservation and ecology through a wider engagement with the social sciences. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.